Genome Characterization of Opuntia ficus-indica: A Simple and Efficient Micromethod - Arnholdt-Schmitt, Birgit; Coe Girão, Luciana; Llamoca-Zárate, Rómulo M.; Campos, Francisco A.P. (Journal of the Professional Association for Cactus Development, 2001)
A rapid and efficient micromethod for DNA extraction of Opuntia ficus-indica plants and subsequent RAPD analysis was established. For extraction, 100 mg of the chlorenchyma from cladodes were used. The DNA quantity extracted was significantly higher than for reported macromethods. Up to 100 ?g DNA per g fresh weight were achieved. RAPD analysis was performed with 10 ng template DNA by using a kit that contains two polymerases and reduces the pipetting procedure to three steps. The method is being applied on a O. ficus-indica cultivar (Gigante) that we are using for studies on somatic embryogenesis and genetic transformation. Fingerprints obtained demonstrated a very high repeatability of the results and homogeneity of our plant material.